A change in social participation affects cognitive function in middle-aged and older Chinese adults: analysis of a Chinese longitudinal study on aging (2011-2018) - Xuyang Li; Wenyan Xu (Frontiers Media S.A., 2024)
BackgroundOne of the biggest challenges facing older adults is cognitive decline and social participation has always been considered a protective factor. However, it is not clear whether social participation predicts cognitive function in this population, rather than depressive symptoms, self-reported health, and activities of daily life, with sufficient capacity to detect unique effects.MethodsThis study included adults aged 45 and above in China (N = 5,258) who participated in a large national older adult health survey and provided data from 2011, 2013, 2015, and 2018. The unique associations between the predictors of social participation and cognitive function over time and context were evaluated in the Latent Growth Model (LGM).ResultsAmong the 5,258 participants in our study, an overall cognitive decline was observed. Social participation predicts two dimensions of cognitive function, with a degree of impact comparable to depressive symptoms, self-reported health, and activities of daily life. Among them, social participation exhibits a noteworthy prognostic impact on episodic memory during the same period. The regression coefficient is approximately 0.1 (p < 0.05) after controlling other mixed variables (depressive symptoms, self-reported health, and activities of daily life). In contrast, social participation is also a significant predictor of mental intactness in the same period, with a regression coefficient of 0.06 (p < 0.05), even if all mixed variables are controlled.ConclusionOver time, the correlation strength of social participation is comparable to other recognized cognitive function prediction indicators, indicating that promoting social participation among middle-aged and older Chinese adults is a meaningful way to improve cognitive function degradation, which has important policy and practical significance.